2005
DOI: 10.2166/wst.2005.0132
|View full text |Cite
|
Sign up to set email alerts
|

Integrated real-time control for a sequencing batch reactor plant and a combined sewer system

Abstract: Integrated real-time control (RTC) concepts, which are trying to operate drainage systems and WWTPs depending on the current capacities of both systems, are becoming more and more important. While almost all publications in this field have been concentrating on continuous flow systems, this paper will present a project which has been initiated to realise an integrated RTC strategy for a Sequencing Batch Reactor (SBR) plant in simulation as well as in full-scale. The results of the simulation are that SBR plant… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 0 publications
0
9
0
Order By: Relevance
“…Of these sensors, COD and ammonia sensors are mainly used to control the aeration period of the SBR process, while phosphate and nitrate sensors are commonly applied during the settling and drawing periods [31]. Some research has established real-time control strategies for a SBR WWTP with sewage systems and a SBR WWTP without sewage systems by applying ammonia, nitrate, and total suspend solid (TSS) sensors [32,33]. It has been shown that real-time control strategies can increase the treatment capability of WWTPs by about 50% while greatly improving the removal efficiency of nitrogen and phosphate.…”
Section: Real-time Control Strategy For the Sbr Process Based On Dirementioning
confidence: 99%
“…Of these sensors, COD and ammonia sensors are mainly used to control the aeration period of the SBR process, while phosphate and nitrate sensors are commonly applied during the settling and drawing periods [31]. Some research has established real-time control strategies for a SBR WWTP with sewage systems and a SBR WWTP without sewage systems by applying ammonia, nitrate, and total suspend solid (TSS) sensors [32,33]. It has been shown that real-time control strategies can increase the treatment capability of WWTPs by about 50% while greatly improving the removal efficiency of nitrogen and phosphate.…”
Section: Real-time Control Strategy For the Sbr Process Based On Dirementioning
confidence: 99%
“…As with most of the SBR plants worldwide, the plant was operated originally with a fixed time-based sequential control strategy (TSC). In order to improve the treatment efficiency and capacity, in 2003 the TSC was replaced by an integrated process-dependent sequential controller (IPSC), which is able to adapt the duration of the treatment steps to the current operating conditions (Wiese et al, 2005a). Therefore, the plant was retrofitted with numerous on-line devices (Table 2).…”
Section: Trends In Ica On Urban Water Systemsmentioning
confidence: 99%
“…Thus, integrated RTC is promising considering environmental and economic aspects, even for rural catchments with less than 10,000 p.e. (Wiese et al, 2005a).…”
Section: State Of and Potential For Ica For Sbr Plantsmentioning
confidence: 99%